EVALUATING THE THERAPEUTIC EFFICACY OF METFORMIN-BERBERINE LOADED NANOPARTICLES FOR THE TREATMENT OF TYPE 2 DIABETES-INDUCED ALZHEIMER’S DISEASE - YADAV, RAVINA; MANI, RUCHI JAKHMOLA; SHARMA, ARUN K.; KUMAR, ASHISH; KATARE, DEEPSHIKHA PANDE (International Journal of Applied Pharmaceutics, 2026)
Objective: To develop and evaluate a novel drug delivery system (NDDS) of Metformin and Berberine-loaded solid lipid nanoparticles (MBSLNPs) for neuroprotection in type 2 diabetes mellitus (T2DM) induced Alzheimer’s disease (AD) model. Methods: MBSLNPs were prepared by hot homogenization and ultrasonication, characterized for particle size, zeta potential, drug loading, and FTIR (fourier transform infrared spectroscopy) compatibility. In vitro release kinetics were modeled, and in vivo efficacy was assessed in a combined streptozotocin (STZ) and amyloid-β (Aβ) rat model by performing behavioral, biochemical, and histopathological analyses. Safety of blank SLNs was evaluated in healthy rats. Results: MBSLNPs exhibited a mean particle size of 102±5 nm, zeta potential of –29±3mV, and high drug loading, with no FTIR incompatibilities. Drug release followed first-order kinetics (R²=0.9955) with Fickian diffusion (n=0.43). In vivo, MBSLNPs significantly improved memory performance in Morris Water Maze and Y-Maze compared with free drug (p<0.01) and disease control (p<0.001). Oxidative stress markers like malondialdehyde (MDA), thiobarbituric acid reactive substances (TBARS) were reduced, while antioxidant enzymes like superoxide dismutase (SOD), glutathione peroxidase (GPx), glutathione (GSH) increased significantly (p<0.01 vs. disease control). Pro-inflammatory cytokines (TNF-α, IL-6, NF-κB) decreased markedly (p<0.001), and acetylcholinesterase (AChE) activity was normalized (p<0.01 vs. free drug) in addition to lower cortical and hippocampal Aβ-40/42 levels in MBSLNP-treated rats (p<0.001). Semi-quantitative histopathology showed significantly reduced neuronal loss and gliosis compared with both disease and free drug groups. Safety evaluation of blank SLNs revealed no significant changes in Serum glutamate oxaloacetate transaminase (SGOT), serum glutamate pyruvate transaminase (SGPT), creatinine, or blood nitrogen (BUN). Conclusion: MBSLNPs demonstrate superior neuroprotective and hepatoprotective efficacy over free drugs, suggesting their translational potential as a combined therapeutic strategy for AD with concurrent liver dysfunction. Thiobarbituric acid reactive substances (TBARS), glutathione peroxidase (GPx), acetylcholinesterase (AChE), serum glutamate oxaloacetate transaminase (SGOT), serum glutamate pyruvate transaminase (SGPT) [26], blood glucose levels, and histological analysis of brain tissue.